Short and long term continuous hydroxylamine feeding in a granular sludge partial nitritation reactor. (1st February 2022) - Soler-Jofra, Aina; Schmidtchen, Lisbeth; Olmo, Lluc; van Loosdrecht, Mark C.M.; Pérez, Julio
Highlights: Low DO promotes hydroxylamine accumulation and N2 O emissions. Ammonium consumption when hydroxylamine is added is impacted by DO. Long term hydroxylamine rate-limiting feeding reduced ammonium consumption. Nitrosomonas remained dominant with hydroxylamine feeding. Abstract: Hydroxylamine is a nitrogen intermediate of ammonium oxidizing bacteria (AOB) that can transiently accumulate during nitrification. The impact of hydroxylamine on aerobic ammonium oxidations is still obscure. In the present study the short and long term impact of hydroxylamine on partial nitritation granular sludge was investigated. Dissolved oxygen was the governing factor determining the hydroxylamine impact in short term studies with continuous hydroxylamine feeding. Continuous short term hydroxylamine feeding together with low dissolved oxygen resulted in higher hydroxylamine accumulation, higher N2 O production and decreased or maintained ammonium consumption. Instead, high dissolved oxygen reduced hydroxylamine accumulation and N2 O production and increased ammonium consumption. Long term continuous hydroxylamine feeding reduced ammonium consumption rate while the constant nitrite production rate indicated that dosed hydroxylamine was mainly transformed to nitrite. This indicates that hydroxylamine was preferred over ammonium as substrate. Nitrosomonas sp. was shown to be predominant during continuous hydroxylamine feeding while the side community shifted. Graphical abstract: Image, graphical abstract